Virus Replication, Cytopathology, and Lysosomal Enzyme Response of Mitotic and Interphase Hep-2 Cells Infected with Poliovirus - Bienz, Kurt (1973)
Mitotic Hep-2 cells, selected by the PEL (colloidal silica) density gradient method and held in mitosis with Colcemid, are readily infected by poliovirus type I (Mahoney). They produce and release the same amount of virus as interphase, random-growing cells. In contrast to interphase cells, mitotic cells show no detectable virus-induced cytopathic effect at the light microscopy level and only slight alterations, consisting of small clusters of vacuoles, at the electron microscopy level. Mitotic cells contain the same total amount of lysosomal enzymes per cell as interphase cells, but they display no redistribution of lysosomal enzymes during the virus infection as interphase cells do. This supports the view that lysosomal enzyme redistribution is associated with the cytopathic effect in poliovirus infection but shows that virus synthesis and release is not dependent on either the cytopathic effect or lysosomal enzyme release. The possible reasons for the lack of cytopathic effect in mitotic cells are discussed.